Plain X-Ray and MRI Evaluation for Prevalence of Lumbo-Sacral Transitional Vertebra in Individuals with Low Backache - Sarshar, Sahar; Javeed, Koukab; Khan, Muhammad Babar; Muhammad, Dost; Hassan, Uzair; Imran, Mohsin Ali (Biological and Clinical Sciences Research Journal, 2025)
Lumbo-sacral transitional vertebra (LSTV) is a common congenital anomaly of the spine that may contribute to chronic low backache due to altered biomechanics and nerve root impingement. The condition is frequently underdiagnosed in routine clinical practice, particularly in low-resource settings where plain radiographs remain the primary imaging modality. Objective: This study aimed to assess the prevalence and morphological types of LSTV among patients presenting with low back pain using plain X-ray and MRI in a CMH Kharian in Pakistan. Methods: This cross-sectional study was conducted at CMH Kharian from April 2024 to September 2024. A total of 58 adult patients aged 18–60 years presenting with chronic low backache underwent both lumbar spine X-rays and MRI scans. LSTV was identified and classified according to the Castellvi classification system. The association of LSTV with clinical symptoms, including pain duration, radiation, and restricted spinal mobility, was evaluated. Data were analysed using SPSS version 26, with a p-value of <0.05 considered statistically significant. Results: LSTV was identified in 25 patients (43.1%) on X-ray and 28 (48.3%) on MRI. Type I and Type II variants were the most commonly observed. MRI demonstrated superior diagnostic sensitivity, identifying additional subtle cases missed by X-ray. A significant association was found between LSTV and prolonged pain duration (p=0.01), the presence of pain radiation (p=0.03), and reduced spinal mobility (p=0.02). These findings underscore the clinical relevance of LSTV in patients with low back pain. Conclusion: LSTV is a prevalent and clinically significant anatomical variation among patients with chronic low back pain in the Pakistani population. MRI is more effective than plain radiography for accurate diagnosis and subtype classification. Routine evaluation for LSTV in chronic low backache cases may lead to more targeted management strategies and improved patient outcomes.